2019
DOI: 10.7554/elife.43653
|View full text |Cite
|
Sign up to set email alerts
|

CCL5 promotes breast cancer recurrence through macrophage recruitment in residual tumors

Abstract: Over half of breast-cancer-related deaths are due to recurrence 5 or more years after initial diagnosis and treatment. This latency suggests that a population of residual tumor cells can survive treatment and persist in a dormant state for many years. The role of the microenvironment in regulating the survival and proliferation of residual cells following therapy remains unexplored. Using a conditional mouse model for Her2-driven breast cancer, we identify interactions between residual tumor cells and their mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 50 publications
(63 reference statements)
1
93
0
Order By: Relevance
“…Residual Her2-driven breast tumors, responsible for cancer recurrence, are characterized by a pro-inflammatory gene expression program, including CCL5 [153]. High levels of CCL5 decreased the time between tumor treatment and recurrence [153]. CCL5 was found to promote tumor recurrence by recruiting CCR5-expressing macrophages, which contribute to collagen deposition in residual tumors.…”
Section: Breast Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Residual Her2-driven breast tumors, responsible for cancer recurrence, are characterized by a pro-inflammatory gene expression program, including CCL5 [153]. High levels of CCL5 decreased the time between tumor treatment and recurrence [153]. CCL5 was found to promote tumor recurrence by recruiting CCR5-expressing macrophages, which contribute to collagen deposition in residual tumors.…”
Section: Breast Cancermentioning
confidence: 97%
“…In breast cancer, a population of residual tumor cells can survive after treatment and persist in a dormant state for many years. Residual Her2-driven breast tumors, responsible for cancer recurrence, are characterized by a pro-inflammatory gene expression program, including CCL5 [153]. High levels of CCL5 decreased the time between tumor treatment and recurrence [153].…”
Section: Breast Cancermentioning
confidence: 99%
“…Along these lines, it was observed that more TNF-, CCL5 and IL-10 are produced by LCLs with higher levels of spontaneous lytic EBV reactivation 74 . These might inhibit the immune control by cytotoxic lymphocytes and recruit immunosuppressive myeloid cells 75 . Indeed, monocytes attracted by CCL5 into the Hodgkin's lymphoma microenvironment support tumor growth in a xenograft model through their immune suppressive activities 76 .…”
Section: Oncogenesis With Lytic Replicationmentioning
confidence: 99%
“…Macrophage adhesion regulated by integrin induces lymphovascular dissemination in BC (55). CCL5 induced recurrence of BC via aggregation of macrophages in residual tumors (56). High expression of mast cells induced the tumor size and the incidence of spontaneous metastasis in BC mice (57).…”
Section: Discussionmentioning
confidence: 99%